The effect of elevated temperatures on excitonic emission and degradation processes of WS2 monolayers. Issue 39 (1st October 2020) - Kaupmees, Reelika; Walke, Peter; Madauß, Lukas; Maas, Andre; Pollmann, Erik; Schleberger, Marika; Grossberg, Maarja; Krustok, Jüri
Abstract : Controlled heating experiments in an inert environment have been performed on WS2 monolayers, in order to clarify the conflicting reports on the high-temperature photoluminescent response of 2D TMDs. Abstract : Controlled heating experiments in an inert environment have been performed on WS2 monolayers, in order to clarify the conflicting reports on the high-temperature photoluminescent response of 2D TMDs. We find that in contrast to some previous results on both WS2 and MoS2, the photoluminescent intensity shows a consistent reduction above room temperature. This is accompanied by an almost linear redshift of the peak maximum, and a nearly linear increase in the peak width, which is attributed to an enhanced interaction with optical phonons. Moreover, by fitting the photoluminescence integral intensity with an Arrhenius type dependence, we demonstrate that the center of the WS2 monolayer flake starts to undergo irreversible degradation at a temperature of 573 K in an inert environment. Regions close to flake edges in contrast, with a more intense room temperature PL response, remain stable. The macroscopic PL signal is largely recovered in these regions following subsequent cooling to room temperature.